PENGARUH KINERJA KEUANGAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA TERHADAP RETURN SAHAM - Sumarno, ' (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 9 No 1 (2014), 2014)
ABSTRACT Financial performance is information acquired regarding company’s internal condition such as portrayed in financial statements. Financial statement information is composed of various ratios such as liquidity,  activity, profitability, and leverage ratios. The purpose of this study was to assess financial performances of national  private banks which have foreign exchange division based on impact of Debt To Equity Ratio (DER), Loan to Deposit Ratio (LDR), Price to Book Value (PBV), Net Profit Margin (NPM), and Operational Expense vs. Operational Income(BOPO) as independent variables to stock return as dependent variable. The population was composed of national private banks which have foreign exchange division actively listed in Indonesian Stock Exchange since 2006 to 2009 and  proper samples taken were 16 out of 36 banks by purposive sampling method. Result of this study showed that all DER, LDR, PBV, NPM, and BOPO variables could be utilized by investors to analyze and predict stock return. DER, PBV, and LDR variables had positive and significant impact on stock return, while BOPO variable had a negative and significant impact on stock return. NPM variable was proven insignificantly affecting stock return. Keywords: BOPO, DER, LDR, NPM, PBV